Inhibition of retinal neovascularization by Dendrobium polysaccharides: a review - Liu, Dan; Chen, Xingwang; Cai, Shanjun (Frontiers in Pharmacology, 2025)
Retinal neovascularization (RNV) is a critical pathological feature of vision-threatening ocular diseases, such as diabetic retinopathy, retinopathy of prematurity, and wet age-related macular degeneration, presenting a persistent therapeutic conundrum. Current clinical treatments primarily rely on anti-vascular endothelial growth factor (VEGF) drugs and laser therapies, which face limitations including drug resistance, high costs, and potential damage to normal tissues. This underscores the need to develop novel therapeutic targets and cost-effective pharmacological interventions with improved safety profiles. Recent investigations highlight Dendrobium polysaccharides (DP), the primary bioactive components of the traditional medicinal herb Dendrobium, as promising multi-target therapeutic candidates. Studies have shown that Dendrobium polysaccharides significantly inhibits pathological angiogenesis by regulating the VEGF signaling pathway, inhibiting inflammatory response and oxidative stress, protecting the extracellular matrix, and reversing intestinal microecological disorders. This review systematically summarizes the structural and functional properties of DP, explores their mechanism of action and experimental evidence in retinal neovascularization, and analyzes their potential as a new therapeutic strategy for retinal diseases. This review also highlights the main limitations of current research: the uncertain relationship between the structure and activity of DP, the differences between pre-clinical models and human diseases, and the potential for structural optimization and the development of delivery systems.